Exploring The Potential Of Coastal Areas In An Effort To Use And Empower Regional Results And Evaluate The Economy Of The Community In The Village Sei Pegantungan Panai Hilir District Labuhanbatu Regency - Novrihan Leily Nasution; Budi Pebriani; Elvina Elvina; Eva Julyanti; Yusmaidar Sepriani; Nurainun Gulo (International Journal Of Community Service, 2022)
This study aims to explain about exploring the potential of the Labuhanbatu Regency area in coastal areas as an improvement and development of the results of coastal areas to be empowered and marketed in the labuhanbatu area itself and at the national level conducted by several academics, namely lecturers of the Faculty of economics to the village government and the community of SEI Pegantungan Village Panai Hilir district. Where in this study also explains the impact of the potential empowerment of coastal areas on the income of village communities, as well as other supporting factors. The method is qualitative descriptive research that is by collecting data through observation, interviews, and documentation of the object of research. Data analysis technique is to use descriptive analysis. The results of this research in Sei Pegantungan village show that first, the increase and development of rice crops as a staple food of the community itself and can also be marketed to other regions as input of local revenue to the government conducted by a lecturer at the Faculty of Economics and Business, University of Labuhanbatu through the establishment of a farming group . Second, the increase in the income of people who participate in farming groups. Third, internal and external factors that support the development carried out by lecturers of the Faculty of Economics and Business, University of Labuhanbatu, village government, and also the SEI Pegantungan Village Community, Panai Hilir district in Labuhanbatu Regency.